2021
DOI: 10.1139/cjpp-2020-0201
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin modulates acute cardiac muscle damage induced by carbon tetrachloride — involvement of oxidative damage, glutathione, and arginine and nitric oxide metabolism

Abstract: The present study was designed to evaluate the cardioprotective effects of melatonin (a single dose of 50 mg/kg), a naturally occurring polypharmacological molecule, in Wistar rats acutely exposed to carbon tetrachloride (CCl4). This was done for the first time by tracking different biochemical parameters that reflect rat heart antioxidative/oxidative capacities, nitric oxide/arginine metabolism, and glutathione cycle. Additionally, the extrinsic apoptosis pathway-related parameters were studied. Acute exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…We and others have demonstrated that cAMP or cGMP, as the important elements of GPCRs, were widely involved in the regulation of cardiac function: both β 1 AR- and β 2 AR-mediated augmentation in cAMP led to the activation of PKA, resulting in positive inotropic and relaxant effects ( 62 , 63 ). In line with our results, Can Ciric Zdravkovic et al ( 29 ) found that DOX inhibited the cAMP/PKA/SIRT1 pathway, which could be attenuated by a Meteorin-like protein. In fact, we have discovered that Gs biased β 2 AR agonist can reduce DOX-induced chronic cardiotoxicity (data not shown here).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We and others have demonstrated that cAMP or cGMP, as the important elements of GPCRs, were widely involved in the regulation of cardiac function: both β 1 AR- and β 2 AR-mediated augmentation in cAMP led to the activation of PKA, resulting in positive inotropic and relaxant effects ( 62 , 63 ). In line with our results, Can Ciric Zdravkovic et al ( 29 ) found that DOX inhibited the cAMP/PKA/SIRT1 pathway, which could be attenuated by a Meteorin-like protein. In fact, we have discovered that Gs biased β 2 AR agonist can reduce DOX-induced chronic cardiotoxicity (data not shown here).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, Tan et al ( 26 ) and Ni et al ( 27 ) highlighted several metabolites as potential biomarkers for DOX-induced acute cardiotoxicity. In fact, metabolic disturbances, such as heme metabolism ( 28 ), carbon metabolism ( 29 ), and oxidative phosphorylation were closely linked to oxidative stress and ROS, which acted as key factors of HF ( 30 ). This was also confirmed by our GSEA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are similar to a previous report ( 66 ). Recent studies have found that the addition of MLT can enhance the cardioprotective effects of mice exposed to carbon tetrachloride and change the activity of glutathione metabolic (glutathione peroxidase, S-transferase, and reductase) enzymes ( 67 ). Liu et al ( 68 ) showed that the addition of MLT can alleviate the oxidative stress of IMD-treated cucumber and increase the activity of glutathione-S-transferase by regulating the ascorbic acid glutathione cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It had been further centrifuged for 30 min at 12,000 g . The supernatant was collected for LPO, inflammatory, cardiac, and in vivo antioxidant marker estimation [ 38 ].…”
Section: Methodsmentioning
confidence: 99%